The quadratic formula is

$\frac{-b \stackrel {+}{-} \sqrt{b^2-4ac}}{2a}$

when the standard form of the equation is $ax^2 + bx +c$

Example

$x^2 + 2x -8$

$a = 1$

$b = 2$

$c = -8$

Substitute these variables into the original equation.

$\frac{-2 \stackrel {+}{-} \sqrt{2^2-4(1)(-8)}}{2(1)}$

$\frac{-2 \stackrel {+}{-} \sqrt{4+32}}{2}$

$\frac{-2 \stackrel {+}{-} \sqrt{36}}{2}$

Now seperate it into two equations

$\frac{-2 + 6}{2}$ and $\frac{-2 - 6}{2}$

$\frac {4}{2}$ and $\frac{-8} {2}$

$x = 2$ and $x = -4$